2009
DOI: 10.1152/ajprenal.90444.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in mice lacking the CXCR3 chemokine receptor

Abstract: The CXC chemokine receptor 3 (CXCR3) has been linked to autoimmune and inflammatory disease, allograft rejection, and ischemic nephropathy. CXCR3 is expressed on endothelial and smooth muscle cells. Although a recent study posited that antagonizing of CXCR3 function may reduce atherosclerosis, the role of CXCR3 in controlling physiological vascular functions remains unclear. This study demonstrates that disruption of CXCR3 leads to elevated mean arterial pressures in anesthetized and conscious mice, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…For example, in vivo studies in normo-and hypertensive humans employing receptor subtype-preferring antagonists suggested that cholinergic vasodilation in forearm resistance vessels is mainly mediated by M 3 receptors (5-6). Similar results have been obtained in pharmacological studies in rat isolated perfused kidneys and in mesenteric vascular preparations from rats and mice (14,(21)(22)(23). Other classical pharmacological studies in the cat middle cerebral artery and in mouse pial arterioles also suggested that M 3 receptors are responsible for cholinergic vasorelaxation in the cerebral circulation (11,38).…”
Section: and M5rsupporting
confidence: 83%
“…For example, in vivo studies in normo-and hypertensive humans employing receptor subtype-preferring antagonists suggested that cholinergic vasodilation in forearm resistance vessels is mainly mediated by M 3 receptors (5-6). Similar results have been obtained in pharmacological studies in rat isolated perfused kidneys and in mesenteric vascular preparations from rats and mice (14,(21)(22)(23). Other classical pharmacological studies in the cat middle cerebral artery and in mouse pial arterioles also suggested that M 3 receptors are responsible for cholinergic vasorelaxation in the cerebral circulation (11,38).…”
Section: and M5rsupporting
confidence: 83%
“…For example, CXCR3-deficient mice exhibit elevated baseline blood pressure, enhanced ex vivo vasoconstriction in response to Ang II, and blunted endothelium-dependent vasodilation compared to wild-type controls (66). These characteristics may be related to augmented AT 1 receptor expression in the vasculature.…”
Section: CXC Chemokinesmentioning
confidence: 99%
“…Following antigen experience, CD8 + T cells lacking CXCR3 preferentially differentiate into memory cells, not short-lived effector cells, thus amplifying the memory pool. CD8 + memory T cells have been implicated in hypertension (87), and augmented memory T cell pools may explain why CXCR3-deficient mice experience exacerbated hypertensive pathology (66). Recent work also highlights the ability of T cells to trans-differentiate between subsets at sites of inflammation (88).…”
Section: Chemokines and Immune Cell Differentiationmentioning
confidence: 99%
“…Unfortunately, blood pressure has only been reported for males in hypertensive mice lacking atrial natriuretic factor, which leads to salt-sensitive hypertension [77] and mice lacking the atrial natriuretic type A receptor, which are hypertensive but not salt-sensitive [78]. Further missed opportunities for understanding sex differences in hypertension include mice lacking the CXC chemokine receptor 3 [79] and 11β-hydroxysteroid dehydrogenase type 2 [80] since only male blood pressure has been reported thus far.…”
Section: Introductionmentioning
confidence: 99%